Recalibrating interpretive authority - Anthea Roberts (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2014)
In newer-style investment treaties, states are increasingly protecting and enhancing their role in interpreting and applying their treaties. This evidences an important shift underway in the investment treaty system: the recalibration of interpretive authority between treaty parties and arbitral tribunals.
Keywords: 330